Policies Supporting Innovation In The European Union In The Context Of The Lisbon Strategy And The Europe 2020 Strategy - Gajewski, Marek (Comparative Economic Research. Central and Eastern Europe, 2017)
In the context of increasing globalization, global competition and rapid change the EU sees innovation and its commercialization as an effective way to build long-term global competitive advantage. Innovation policy is a link between research and technological development policy and industrial policy and makes it possible to create conditions conducive to bringing ideas to the market. It is also closely linked to other EU policies regarding e.g. employment, competitiveness, environment, industry and energy. This paper presents the evolution, conditions and objectives of the innovation policy of the European, and describes the main assumptions of the Lisbon and Europe 2020 strategies. Additionally it indicates possible ways of assessing the measures undertaken within the above-mentioned policies and of determining the tools necessary to implement the strategies.